Determining service quality indicators to recruit and retain international students in Malaysia higher education institutions: global issues and local challenges - Hussein Amzat, Ismail; Najimdeen, Abdul Hakeem Alade; Walters, Lynne M.; Yusuf, Byabazaire; Padilla-Valdez, Nena (MDPI, 2023)
International student mobility has become an effective global strategy for tertiary institutions’ economic growth, revenue, and diversity. This study aimed to provide service quality indicators that can be used to improve international student mobility services in Malaysian public universities. The sample comprised international students in Malaysia, with 1273 students from 76 countries participating. The SERVQUAL model and instrument were used, and the indicators were determined using the measurement model (MM) and Analytic Hierarchy Process (AHP). The findings of MM and AHP ranked courtesy and communication as the highest indicators, and AHP found that soft skills were required to improve service quality at Malaysian higher education institutions. These findings contribute to understanding what is needed to improve the university quality service system in Malaysian public universities. The results also apply to other universities, especially Southeast Asian countries involved in internationalisation practices. Practical implications were provided to improve internationalisation service quality at colleges and universities, with suggestions for future study.